The placement journey: Do year one placement modules support Childhood Studies students' professional development?. Issue 2 (November 2017) - Brown, Zeta; Edwards, Tracey; Perkins, Helen
This study investigated changes made to the Childhood Studies placement journey of one post-1992 University in England. The Childhood Studies degree includes 'practitioner options' that requires students to complete 200 h placement experience, including 50 h in year one. In 2014, the participant university responded to this expectation by developing a year one placement module. The study sought to investigate whether the placement module supported the development of student's professional identities in the first year of their studies. The study primarily used questionnaires, with a small amount of interviews and focus groups during 2014–2015. It found three key themes that students associated with their year one placement and their professional development. These were the importance of placement, links made from theory to practice and links from practice to theory. Students did however state disparities in their experiences of placement, especially in the range of responsibilities they were given. Students commented generally on the benefits (to their professional development) of relating theory to their year one practice, but noted frustration that there were minimal opportunities to reflect on practice in module assessments. The study contributes to existing literature by questioning how theory to practice and practice to theory links can be made more explicit in year one programmes.